The coral reef health at surrounding blue swimming crab fishery sites in Mandangin Island, East Java, Indonesia. Issue 1 (December 2021) - Ardiansah, I; Hidayat, S A; Mutmainah, D F D; Siahaan, M C B; Firdaus, M R; Subhan, B; Madduppa, H
Abstract: Blue swimming crab fishery activities very often do not put into account the environmental condition. Coral reef, as one of the blue swimming crab habitats, can be affected by these activities. This study aims to determine the effect of blue swimming crab fisheries on coral health in Mandangin Island, East Java, Indonesia. Data collection points are determined based on the results of interviews by participatory mapping. Water quality data includes visibility, temperature, salinity, pH, DO, current velocity. Collecting coral reef data were using Line Intercept Transect (LIT), while for reef fish Underwater Visual Census (UVC) were used. The coral health index was determined based on the relevance between benthic components and fish components. The average of Mandangin Island's water quality is in accordance with the quality standards of the Indonesian Minister of Environment Decree No.51 of 2004. Hard coral cover and fish biomass are classified as low, but the value of resilience is high. The coral reef health index value on Mandangin Island is 3.